Mecanismes De Contamination Des Eaux Souterraines Dans Le Secteur Du Lac Mbeubeuss, Dakar, Senegal - Florent, Essouli Olivier; AÃ¯ssatou, Gladima-Siby Sophie; TimothÃ©e, Miyouna; Laurent, Matini; Serigne, Faye (European Scientific Journal, ESJ, 2018)
The physicochemistry of groundwater in the immediate environment of the dump, and its surroundings, shows that the true value of the electrical conductivity of groundwater is close to 2000 Î¼S / cm. The value of electrical conductivity that is greater than 2000 Î¼S / cm demonstrates groundwater contamination through the Mbeubeuss Lake landfill, with chemical groundwater facies dominated by Sodium Chloride, Potassium Chloride, and Calcium Chloride. The study of the unsaturated zone of the aquifer and the relationship between the major chemical elements of groundwater, rainwater, and seawater made it possible to specify, on one hand, the sources of mineralization of the groundwater at the Mbeubeuss Lake site and its surroundings. Indeed, the situation close to the sea would suggest a considerable intake of salts by aerosols and sea spray. Based on contribution to this study, the influence of the old sediments of the dry Lake Mbeubeuss and the percolation of leachates resulting from the decomposition of garbage landfilled under the action of rainwater would be added. On the other hand, this study also made it possible to determine the main processes of controlling the mineralization of groundwater. This includes the marine inputs, the dissolution-precipitation of clay minerals present in the geological formations constituting the aquifer, the dilution- concentration, evaporation, and anthropogenic pollution.